EXPLORATION OF THE DEATH CEREMONY OF THE TOBA BATAK TRIBE - Tiarnita Maria Sarjani Siregar; Halimahtu Saddiah; Ami Girsang; Ribka Hawkins Manurung (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2024)
Death is an inevitable part of human life. For the Toba Batak tribe, death is not the end, but a transition to the afterlife. This article examines the depth of Toba Batak traditions and beliefs regarding death ceremonies and the types of death known in Toba Batak culture. The Toba Batak tribe living in the North Tapanuli region, North Sumatra, Indonesia, has a rich and complex death system that reflects a rich cultural heritage and deep values. Exploring the types of death that are recognized and respected in the daily lives of the Toba Batak people, this article tells how they see the realm of death and respond to it through various ceremonies. Each type of death has a place, from death due to old age to death due to accidents or violence. This article provides an in-depth overview of how the Toba Batak people celebrate, respect and respond to death in everyday life.